2023
DOI: 10.1097/ede.0000000000001691
|View full text |Cite|
|
Sign up to set email alerts
|

Medicaid Expansion and Racial–Ethnic and Sex Disparities in Cardiovascular Diseases Over 6 Years: A Generalized Synthetic Control Approach

Roch A. Nianogo,
Fan Zhao,
Stephen Li
et al.

Abstract: Background: Studies have suggested Medicaid expansion enacted in 2014 has resulted in a reduction in overall cardiovascular disease (CVD) mortality in the United States. However, it is unknown whether Medicaid expansion has a similar effect across race–ethnicity and sex. We investigated the effect of Medicaid expansion on CVD mortality across race–ethnicity and sex. Methods: Data come from the behavioral risk factor surveillance system and the US Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Quasi-experimental study designs employ the approximate randomness of factors related to exposure (eg, the timing of a policy implementation) to evaluate the effect of a policy, accounting for time-fixed confounders by design ( 17-19 ). With the appropriate data, including pre-expansion and postexpansion data on cancer mortality and time-varying confounders, these methods can and have been used to successfully evaluate the effect of Medicaid expansion on mortality from cancer ( 20 ) and cardiovascular disease ( 21 ). Rigorous quasi-experimental methods can also be used to evaluate the health-related effects of housing policies.…”
mentioning
confidence: 99%
“…Quasi-experimental study designs employ the approximate randomness of factors related to exposure (eg, the timing of a policy implementation) to evaluate the effect of a policy, accounting for time-fixed confounders by design ( 17-19 ). With the appropriate data, including pre-expansion and postexpansion data on cancer mortality and time-varying confounders, these methods can and have been used to successfully evaluate the effect of Medicaid expansion on mortality from cancer ( 20 ) and cardiovascular disease ( 21 ). Rigorous quasi-experimental methods can also be used to evaluate the health-related effects of housing policies.…”
mentioning
confidence: 99%
“…Regarding the paper by Nianogo et al in the March issue of EPIDEMIOLOGY, 1 the authors have identified some typographical errors in the reporting of Table 1 in the results section under baseline characteristics on Page 267 and in the reporting of the confidence interval pertaining to the effect of Medicaid among men on Page 268. The correct paragraphs (with bolded text) should be as follows:…”
mentioning
confidence: 99%